Role of Ultrasound and Color Doppler in Assessment of Thyroid Nodules: Ultrasound and colour doppler for thyroid nodules - Ishtiaq, Sadia; Arshad , Nosheen; Ali, Abid; John, Akash; Abeeha, . (Pakistan BioMedical Journal, 2022)
Thyroid nodules, both macroscopic and microscopic, are widespread in the general population with up to 80% of people having them at autopsy. Ultrasonography is now widely available to diagnose thyroid nodules. Objective: To determine the role of ultrasound and colour doppler in assessment of thyroid nodule. Methods: This cross-sectional study was conducted at Aziz Bhatti Shaheed Teaching Hospital Gujrat, Pakistan from 1st February to 20th June, 2022. In this study total 70 patients with thyroid nodules were included who visited the hospital OPD with the complaint of neck pain and difficulty in swallowing. It included individuals with all ages of wither gender. People with the history of previous neck surgery were excluded. A linear high frequency transducer was used on Toshiba Aplio XG ultrasound machine. Data were analysed by SPSS version 22. Results: Total 70 patients were included in this study. Their age ranged from minimum 25 to maximum 74 with median age 47.50 years. As regard age, the mean age of study population was 46.057 ± 11.910. The diagnosis was confirmed by ultrasound and color doppler. As regard ultrasound findings, we classified type of nodule as irregular nodule (n) 2.9%, left solitary nodule (n) 21.4%, right solitary nodule (n) 30.0%, isthmus nodule (n) 7.1%, multi-nodule goiter (n) 18.6%, bilateral nodule (n) 10.0%, heterogenous thyroid nodule (n) 7.1%, complex thyroid nodule (n) 2.9% were present. As regard color doppler flow present in (n) 32.9% and no flow seen in (n) 67.1%. Conclusions: Ultrasound is a rapid and secure way to evaluate thyroid nodules. It is the most accurate and cost-effective method for evaluating and monitoring thyroid nodules.